Estimation of Variability, Heritability, and Genetic Advance among Ethiopian Coriander (Coriandrum sativum L.) Accessions - Wegayehu Tilahun, Gizaw; Galalcha, Dasta Tsagaye; Mengistu, Fekadu Gebretensay; Limeneh, Demis Fikire; Zeleke, Awoke Ali; Hundie, Nimona Fufa (International Journal of Bio-resource and Stress Management, 2023)
The objective of this study was to assess the extent of variability of yield and yield-related traits, heritability, and genetic advances among Ethiopian coriander accessions. The experiment was conducted at Kulumsa Agricultural Research Center, Southeast Ethiopia, during 2019- 2020 cropping seasons. Twenty-five Ethiopian coriander accessions were tested in a 5 x 5 simple lattice design with two replications; and data were collected on eight yield and yield-related traits. The combined analysis of variance revealed highly significant differences (P<0.01) between coriander accessions for each trait. The results showed a wide range of variability in all studied traits, indicating the potential for simultaneous improvement of yield and yield-related traits. The heritability (H2b) estimates ranged from low for seeds per umbellet and thousand seed weight to very high, for seed yield per hectare and number of umbels per plant in the first and second cropping season, respectively. The highest genetic advances as a percentage of the mean (GAM (%)) were observed for seed yield per plant, seed yield per hectare, and number of umbellets per umbel. These findings suggest that cultivar selection based on these traits with high H2b coupled with GAM (%) could enhance progeny performance and increase the productivity and profitability of coriander. Therefore, the results had practical implications for coriander breeders and farmers in Ethiopia and could contribute to the development and sustainable coriander farming practices. Further investigations are necessary to identify superior accessions with desirable processing qualities, assess the phenotypic and genotypic diversity among Ethiopian coriander accessions.